Fighting the Cause of Alzheimer’s and GNE Myopathy - Devi, Shreedarshanee; Yadav, Rashmi; Chanana, Pratibha; Arya, Ranjana (Frontiers in Neuroscience, 2018)
Age is the common risk factor for both neurodegenerative and neuromuscular diseases. Alzheimer disease (AD), a neurodegenerative disorder, causes dementia with age progression while GNE myopathy (GNEM), a neuromuscular disorder, causes muscle degeneration and loss of muscle motor movement with age. Individuals with mutations in presenilin or amyloid precursor protein (APP) gene develop AD while mutations in GNE (UDP N-acetylglucosamine 2 epimerase/N-acetyl Mannosamine kinase), key sialic acid biosynthesis enzyme, cause GNEM. Although GNEM is characterized with degeneration of muscle cells, it is shown to have similar disease hallmarks like aggregation of Aβ and accumulation of phosphorylated tau and other misfolded proteins in muscle cell similar to AD. Similar impairment in cellular functions have been reported in both disorders such as disruption of cytoskeletal network, changes in glycosylation pattern, mitochondrial dysfunction, oxidative stress, upregulation of chaperones, unfolded protein response in ER, autophagic vacuoles, cell death, and apoptosis. Interestingly, AD and GNEM are the two diseases with similar phenotypic condition affecting neuron and muscle, respectively, resulting in entirely different pathology. This review represents a comparative outlook of AD and GNEM that could lead to target common mechanism to find a plausible therapeutic for both the diseases.